THE ROLE OF ISLAMIC CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL, ISLAMICITY PERFORMANCE INDEX ON THE PROFITABILITY ISLAMIC BANK IN INDONESIA - Surepno Surepno; Muhammad Qoes Atieq (Universitas Sultanah Nahrasiyah, 2025)
This study aims to analyze the influence of Islamic Corporate Governance (ICG), Intellectual Capital (IC) and Islamicity Performance Index (IPI) to profitability of Islamic Banks in Indonesia. Research this is type study quantitative with population used​ as many as 14 Islamic Commercial Banks in Indonesia. The selection method sample use purposive sampling and obtained 9 samples of Islamic Commercial Banks that meet the requirements criteria. Data analysis techniques in study This use analysis statistics descriptive, analysis multiple linear regression and testing hypothesis. The results obtained show Islamic Corporate Governance which is proxied by the disclosure of the Structure and Working Mechanism of the Sharia Supervisory Board (SSB), the Structure and working mechanism of the Board of Directors and SSB have an impact on the performance of Islamic Banks. Intellectual Capital partially has no effect on the profitability level of Islamic Banks. This means Intellectual Capital not yet able to provide value Added on expenses for Human Resources Capital, Customer Capital and Structural Capital so as to be able to improve performance finance proxied by ROA. Islamicity performance index proxied by EDR and profit sharing significantly influence the profitability of Islamic Commercial Banks, while other proxies proved insignificant.